Investment in Health in Times of COVID -19 and its Impact on Nursing Care - Rodas Rivera, Alejandra (2024)
Objective: To explain the investment in health in times of COVID-19 and its impact on nursing care. Development: The Peruvian Government allocated fiscal resources to face the pandemic, however, this was insufficient, reflected in shortages of hospital beds, personal protective equipment, essential supplies and human resources in health. Added to this, the workforce of nursing professionals who were left to face the pandemic increased due to comorbidity licenses of colleagues, which ultimately exacerbated infections. The vulnerability of nursing became notorious; they experienced insecurity due to threats and violence from patients and family members due to the scarcity of resources and the urgent need for care. Conclusion: Investment in health in times of COVID-19 was not sufficient to address the health crisis, due to the complex processes that configured the purchase of equipment, supplies and medicines, this led to a weakening of nursing to provide quality care and protect themselves from the deadly virus. The lack of investment not only undermined care, but also discrimination by government authorities by not including nursing in decision-making at the working groups to combat COVID-19. It is necessary to recognize that investing in nursing is investing in the future of everyone's well-being.